Little Green - Baker, Keith, 1953- (New York : Red Wagon Books, 2005)
A young boy paints the flight of a hummingbird as it zips, loops, and zigzags around his garden.
Cover title.
Board book.
Keywords: Hummingbirds -- Fiction; Stories in rhyme; Hummingbirds -- Juvenile fiction